ANTONI MALCZEWSKI – DUCH ROMANTYCZNY ZANURZONY W TRADYCJI. O MARII - Stelmaszczyk, Barbara (Colloquia Litteraria, 2017)
The article offers a new reading of Antoni Malczewski’s poetic novel Maria as an innovative – in terms of its form – work of early Romanticism. The author argues that the form of a classicist historical narrative was essentially modernized through the exemplary Romantic construction of the narrator (characteristic of syncretic genres in Romanticism) as well as an innovative – as far as Byron’s model is concerned – project of a Romantic hero. Furthermore, Malczewski’s narrative poem is presented by the author as the most accusatory text among the early Romantic new poetry works. Stelmaszczyk claims that it targets the socio-political system of old Poland that violated the balance of social forces and lead to the demise of ethos, which in turn resulted in the destruction of individual heroes, annihilation of moral values, and the emergence of deep pessimism that overshadowed the future fate of people. That pessimism is quoted as the reason behind the negative reception of Malczewski’s narrative poem among his contemporaries.